FINANCING OF INVESTMENT PROJECTS OF GAS DISTRIBUTION ENTERPISES AS A FACTOR OF THEIR DEVELOPMENT - Korol , S. V. (The actual problems of regional economy development, 2016)
In the article theoretical questions of formation sources of financing investments are considered, the analysis of investment activities is carried out by the sources of funding for gas utility. The purpose of this article is to identify priority sources of financing investment activities of gas distribution enterprises. The methodology of research. To achieve this goal the author used methods of theoretical generalization; statistical and financial methods in the study of dynamics and structure of investment; tabular methods to display the structure of the main sources of financing of the investment program of gas distribution enterprises; consistency and comparison, to determine the relationship between the main components of investment sources of financing. Results. As a result of research by critical retrospective analysis to determine the structure of sources of financing investment activities of gas distribution enterprises. It is established that the main sources of financing the investment program are the tariffs for transportation and supply of gas, says the national Commission, carrying out state regulation in the areas of energy and utilities (NCREU). It is filed the structure of the main financing sources of the investment program of gas distribution enterprises. It is proved that the level of funding depends on the size of NCREU rates and gas consumption. Scientific novelty of the article is lack in domestic and foreign areas of research priority selection of sources financing of the investment program for gas distribution enterprises. The practical significance is that the theoretical concepts, practical results and conclusions of articles that reveal the essence of the problem of investment sources of financing, can be used in the activity of gas distribution enterprises taking into account the current state of development of the economy. JEL: M 20